2001
DOI: 10.1002/1521-396x(200110)187:2<499::aid-pssa499>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Sputter-Metallization-Induced Electronic Defects in Thermal SiO2

Abstract: The generation of interface states and oxide electron traps in thermal silicon dioxide (SiO 2 ) layers by sputtering metallization has been investigated. The dependence of the samples on electric field and temperature during the sputter process is observed. The interface state density spectra revealed narrow distributions indicating an increased density of band edge states. In the upper part of the Si band gap a peak was observed due to the generation of a particular interface defect site. Three bulk defect ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Although the nature of interface traps is doubtless dependent on intricate microstructural details of the interaction between the semiconducting and dielectric layers, the interface trap density can be qualitatively understood from a chemical perspective (Figure ). It is known that, in the absence of special surface modifications, Bare substrates exhibit an interface trap density of ∼10 12 cm -2 which is principally attributed to interfacial chemical functionalities/species such as Si−OH, in conjunction with adsorbed H 2 O, and adventitious carbon contamination. , Such chemical defects can affect charge transport by deep-trapping/doping and/or by scattering carriers at the semiconductor−dielectric interface, and this effect is reflected in device performance parameters. Such interfacial effects are important in organic semiconductor-based devices since the charge transport process is believed to occur within the very first few semiconducting layers in proximity to the gate dielectric .…”
Section: Discussionmentioning
confidence: 99%
“…Although the nature of interface traps is doubtless dependent on intricate microstructural details of the interaction between the semiconducting and dielectric layers, the interface trap density can be qualitatively understood from a chemical perspective (Figure ). It is known that, in the absence of special surface modifications, Bare substrates exhibit an interface trap density of ∼10 12 cm -2 which is principally attributed to interfacial chemical functionalities/species such as Si−OH, in conjunction with adsorbed H 2 O, and adventitious carbon contamination. , Such chemical defects can affect charge transport by deep-trapping/doping and/or by scattering carriers at the semiconductor−dielectric interface, and this effect is reflected in device performance parameters. Such interfacial effects are important in organic semiconductor-based devices since the charge transport process is believed to occur within the very first few semiconducting layers in proximity to the gate dielectric .…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest that OA as the stabilizing ligand is effectively bound to surfaces of the inorganic nanoparticle cores and nearly no free OA is present in the nanoparticle suspensions. It has been shown that alkyl chains on modified dielectric surfaces can substantially reduce the interfacial trappes-state density ,, , which is principally attributed to interfacial chemical functionalities/species such as Si−OH for SiO 2 dielectrics, in conjunction with adsorbed H 2 O and adventitious carbon contamination , . It has been found that silanol groups cannot be completely removed by such self-assembled alkyl layers .…”
Section: Resultsmentioning
confidence: 99%
“…Shifts in V FB , which are ideally zero at room temperature, ensue for Pd and Au gates from differences in their respective work functions ͑0.04 V͒, as well as dielectric traps and surface states promoted 16 by the sputtering process,…”
Section: Experimental Details and Proceduresmentioning
confidence: 99%